Serum Mineral Profile in Holstein Friesian Crossbred Cows with Normal and Low Solids-not-fat Milk Syndrome - Nyamagonda, Hanamanta; Swamy, Muniyappa N.; Kalmath, Gurubasayya P.; Rao, Suguna; Ramesh, Pujari T.; Isloor, Srikrishna; Veena, Malavalli P. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
A study was undertaken to compare the serum mineral profile in Holstein Friesian crossbred cows with low solids-not-fat (SNF) syndrome and normal SNF content during 4th and 8th week of 3rd and 5th lactations. A total of 24 cows were selected for the present study and based on the SNF content in their milk, the animals were divided into four groups, viz., Group I (>8.5% SNF milk in 3rd lactation), Group II (< 8.5% SNF milk in 3rd lactation), Group III (>8.5% SNF milk in 5th lactation) and Group IV (<8.5% SNF milk in 5th lactation) with six animals in each group. The blood samples collected at 4th and 8th weeks of lactation from all the selected animals were processed and serum samples were stored at -20°C till completion of the study. Stored serum samples were later utilized for determination of serum calcium, phosphorus, sodium, potassium, and magnesium with the help of autoanalyzer using specific reagent kits. Serum phosphorus and sodium levels were significantly (p<0.05) higher, and the serum potassium levels were significantly (p<0.05) lower in normal (>8.5%) SNF content cows compared to low SNF (<8.5%) syndrome cows at 4th and 8th weeks of 3rd and 5th lactations. However, the serum calcium and magnesium levels did not differ significantly between the groups. It was concluded that the significantly lower levels of serum sodium and phosphorous in cows with low SNF could be one of the contributing factors for the low SNF content.